THE CORRELATION AMONG DURATION OF ORAL CONTRACEPTION WITH THE INCIDENCE OF MELASMA IN SUMBERWUDI, LAMONGAN, EAST JAVA, INDONESIA - Dina Sulviana Damayanti; Putu Irma Pratiwi; Gracea Petricka (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: An increasing of estrogen in the body including consumption certain pills, excessive exposure to sunlight, or even by pregnancy, may cause various effects such as as melasma, brown pigmentation that can occur in women, appeared in certain organs Aims: The objective was to analyse the relationship between duration of use of oral birth control pills combined with the occurrence of melasma. Methods: This is an analytical research using cross-sectional approach involved 17 respondents who were selected by a purposive sampling technique. Inclusion criteria for this study was as acceptor oral pill combinations at least 30 days or have taken one blister. In this study, the research instrument used was an open questionnaire and observation. Data was then analysed by parametric statistic using fisher's exact. Results: The results found the combined oral pill acceptors complained emergence of black spots on the face in a period of more than 2 years of use whereas previously unheard. Conclusion: Based on the results, health workers in the provision of counselling to patients about the side effects of the combined oral pill black spots face (melasma). Thus, acceptors got enough for knowledge and able to cope with the occurrence of dark spots face (melasma).